Quantifying deep cryogenic treatment extent and its effect on steel properties. (1st October 2021) - Funk, Paul A.; Kanaan, Ahmed; Shank, Christine; Cooke, Peter; Sevostianov, Igor; Thomas, Joe W.; Pate, Michael O.
Abstract: Deep cryogenic treatment (DCT) has been known since the 1930s to improve hardness, fatigue resistance, and wear resistance of steel. While the effect of DCT on wear properties has been well documented, there is no consensus regarding the causal mechanisms, nor a widely accepted quantitative description of them. DCT transforms retained austenite into martensite and triggers the precipitation of fine carbides, among other things. We observed that DCT had a negligible effect on Young's modulus and the yield limit of high carbon spring steel. The observed microstructural changes (presence of specific dendritic inhomogeneities typical for inclusions of austenitic phase in non-treated specimens and homogeneous microstructure of treated ones) can serve for qualitative purposes only. However, we found that DCT led to a decrease in steel electrical resistivity which can be explained by noticeable differences between the resistivities of the martensitic and austenitic phases. We propose a micromechanical model for electrical resistivity which allows monitoring of the content of retained austenite and postulate that it can be used for other materials as well. We also observed increased resistivity after mechanical loading of the specimens, correlating with increased dislocation density caused by loading. This quantity can be used to assess the average dislocation density.